Bullous systemic lupus erythematosus in a 10-year-old child - Nelise Ritter Hans-Bittner; Guilherme Canho Bittner; Günter Hans Filho; Luiz Carlos Takita (Sociedade Brasileira de Dermatologia, 2017)
Abstract: Bullous systemic lupus erythematosus (BSLE) is a rare autoimmune subepidermal blistering disease, with few cases described in childhood. It has different clinical-pathological features. We report a case of BSLE in a 10-year-old child with systemic lupus erythematosus, treated with prednisone and hydroxychloroquine. There was complete remission with dapsone, with no recurrence of skin lesions throughout one year of follow-up. We highlight the rarity and early age of occurrence.